Managerial consensus on competences: a case study of top- and middle managers in Koivu Company - Benedek, Melinda Beáta (My University, 2012)
Since the rise of the resource-based view of firms, competences have been widely studied as part of strategic management studies. However, there was a gap in research focusing on the consensus between managers at different levels of a corporation regarding competences. In this thesis, the dimensions of consensus (locus, content, scope and degree) are used to analyze the extent of consensus among top- and middle managers of a particular company. The study has three research questions. The first research question focuses on the extent of consensus among individual top managers on the contents of organizational core competence, key individual competence and competence management. The second research question focuses on the extent of consensus among individual middle managers on the same three issues. Finally, the third research question aims to investigate the extent of consensus between the groups of top- and middle managers. To complete the research, a qualitative interview study was conducted on the top- and middle managers of a Finnish company. The interviewees represented the firm’s headquarters and the Hungarian strategic business unit. Nine semi-structured interviews were conducted in order to complete the study. The extent of consensus among the members of the top management team is not as wide and strong as it is suggested in the strategic management literature, and the top management team may not be the primary locus of consensus in an organization even though it is their group that decides about and formulates corporate strategy. On the other hand, higher degree of consensus was found among the members of the middle management team, and this team found to be the primary locus of consensus in the current study. Furthermore, the research found that top- and middle managerial perceptions do not necessarily differ because of the organizational level differences. On the other hand, the professional background of managers seemed to have an impact on their perceptions in the given contents.
Keywords: Strategic Management; Competence-Based View; Managerial Consensus; Managerial Perception; Core Competence; Individual Competence; Competence Management; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|